Integrated Criminal Policy: Pelaksanaan Pidana Mati Pada Tindak Pidana Korupsi Pasca Kepres Nomor 12 Tahun 2020 - Jusafri Jusafri; Nur Hidayani Alimuddin; Faisal Herisetiawan Jafar (Pusat Riset dan Inovasi Nasional, 2022)
The criminal acts of corruption that occurred against funds for dealing with the Covid-19 pandemic raise the question of whether the death penalty can be applied to perpetrators of criminal acts of corruption. The aim of this research is to see the potential for applying the death penalty in cases of criminal acts of corruption with integrated criminal policy after the issuance of Presidential Decree of the Republic of Indonesia Number 12 of 2020 concerning the Determination of Non-Natural Disasters for the Spread of Corona Virus Disease 2019 (Covid-19) As a National Disaster. This research is normative legal research based on data collection, namely literature study and using a legal approach and theoretical approach in studying the issues in this research. The death penalty cannot be implemented or threatened against perpetrators of criminal acts of corruption regarding funds for dealing with the Covid-19 based on Presidential Decree 12/2020 considering the differences in the phrases